Captive gods: religion and the rise of social science - Appiah, Kwame Anthony (Terry Lectures series, 2025)
"Philosopher Kwame Anthony Appiah explores how early social scientists developed our modern understandings of society through their theories of religion. The foundations of modern social science were built on the study of religion, the acclaimed thinker Kwame Anthony Appiah argues. Delving into the intellectual currents of the nineteenth and early twentieth centuries, he investigates how formative thinkers -- notably Edward Burnett Tylor, âEmile Durkheim, Georg Simmel,and Max Weber -- grappled with the concepts of society and religionas interdependent categories. Appiah shows how their efforts to define religion, or evade the task, mark the power and limitations of social thought in ways that persist among theorists today. Religion was not merely an object of study but a framework through which earlysocial scientists established sociology as a discipline. Appiah also examines more recent work in both interpretive sociology and evolutionary and cognitive psychology about the mechanisms through which communities form beliefs and values -- while underscoring the enduring significance of these earlier debates for contemporary social thought. Throughout, he intertwines storytelling, historical analysis, and philosophical reflection to show how our ideas about society andculture have been, and continue to be, forged in dialogue with religious questions."--